Cosmetic outcome of implantation of cross-linked human acellular dermal matrix after parotidectomy. Issue 4 (May 2019) - Kim, D.Y.; An, S.H.; Woo, J.H.; Baek, M.K.; Kang, I.G.
Abstract: Although skin depression after parotidectomy affects the patient's satisfaction with cosmesis we know of little research about it, so we attempted to alleviate it by inserting human acellular dermal matrix (hADM) after the operation. We made a retrospective analysis of the casenotes of 63 patients who were diagnosed with parotid tumours and were operated on between January 2015 and December 2016. Factors that affect satisfaction with cosmesis, including the use of hADM, sex, age, incision, size of tumour, sample size, complications, and the name of the surgeon were recorded and evaluated on a scale from 1 (most unsatisfactory) to 10 (very satisfactory), and the satisfaction according to each factor was compared. The mean (SD) follow-up period was 13 (6) months, and 19 of the 63 patients developed complications. Satisfaction was significantly better when hADM had been inserted (p = 0.0008), when the patient was female (p = 0.033), or there were no complications p = 0.0161). On linear regression analysis, all three factors showed a significant causal relation with satisfactory cosmesis. Insertion of hADM after operations on the parotid gland seems to be effective in improving this by preventing skin depression.